2017
DOI: 10.1152/japplphysiol.00977.2015
|View full text |Cite
|
Sign up to set email alerts
|

Acute intermittent hypoxia in rats activates muscle proteolytic pathways through a gluccorticoid-dependent mechanism

Abstract: Although it is well known that chronic hypoxia induces muscle wasting, the effects of intermittent hypoxia on skeletal muscle protein metabolism remain unclear. We hypothesized that acute intermittent hypoxia (AIH), a challenge that activates the hypothalamic-pituitary-adrenal axis, would alter muscle protein homeostasis through a glucocorticoid-dependent mechanism. Three-week-old rats were submitted to adrenalectomy (ADX) and exposed to 8 h of AIH (6% O for 40 s at 9-min intervals). Animals were euthanized, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
(68 reference statements)
1
5
0
1
Order By: Relevance
“…With this previously documented pattern (Lightman, 2008;Sawchenko et al, 1984) in mind, it is perhaps not surprising that a significant fraction of activated MP neurons (~30%) contained CRH, while a small minority (~2%) contained AVP. Together with existing literature evidence (Ma et al, 2008;Przygodda et al, 2017;Xing and Pilowsky, 2010), these findings suggest that MP CRH neurons could represent a synaptic nodal point within an AIH responsive network. Insight into the circuitry activated by AIH has been provided in a recent report (Kim et al, 2018), which revealed a critical role for the circulating hormone angiotensin II (AngII) in triggering AIHinduced sLTF.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…With this previously documented pattern (Lightman, 2008;Sawchenko et al, 1984) in mind, it is perhaps not surprising that a significant fraction of activated MP neurons (~30%) contained CRH, while a small minority (~2%) contained AVP. Together with existing literature evidence (Ma et al, 2008;Przygodda et al, 2017;Xing and Pilowsky, 2010), these findings suggest that MP CRH neurons could represent a synaptic nodal point within an AIH responsive network. Insight into the circuitry activated by AIH has been provided in a recent report (Kim et al, 2018), which revealed a critical role for the circulating hormone angiotensin II (AngII) in triggering AIHinduced sLTF.…”
Section: Discussionsupporting
confidence: 78%
“…Here, we quantified AIH-induced recruitment of PVN neurons by exposing awake rats to graded intensities of AIH and used immunostaining for the immediate early gene product c-Fos to map the regional and rostro-caudal distribution of transcriptionally activated PVN neurons. Intermittent hypoxia has been linked to activation of endocrine and autonomic components of the stress axis (Hwang et al, 2017;Ma et al, 2008;Przygodda et al, 2017;Wang et al, 2004;Zoccal et al, 2007), and because stress axis activation can enhance specific forms of synaptic plasticity that may contribute to sLTF (Arango-Lievano et al, 2015;Peters et al, 2018;Schierloh et al, 2007), we used dual immunostaining to determine the extent to which individual AIH-activated (c-Fos positive) PVN neurons contained the stress-regulatory neuropeptides corticotropin releasing hormone (CRH) and arginine vasopressin (AVP). We found that AIH robustly induced c-Fos amongst CRH containing, but not AVP containing, neurons located in the rostral half of the PVN's medial parvocellular subdivision, suggesting this population of CRH neurons could contribute to AIH-induced sLTF neuroplasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is tempting to speculate that progressive recruitment of the PVN during exposure to AIH could reflect gradually increasing RAAS activation of SNA, which could operate together with or instead of gradually increasing arterial chemoreceptor activation at later cycles of AIH. It should also be stressed that acute hypoxia and hypotension strongly stimulate the hypothalamopituitary-adrenal stress axis (5,36), and the resulting increase of plasma corticosterone could have contributed to net increases of SNA by attenuating arterial baroreflex transmission through the NTS (41).…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent hypoxia, the unique characteristic of sleep apnea, is caused by repeated upper airway collapse during sleep in patient with obstructive sleep apnea (OSA) [ 5 ], and is generally divided into acute intermittent hypoxia (AIH) and chronic intermittent hypoxia (CIH) according to its cumulative duration. Previous studies have suggested that the cumulative duration of AIH should not exceed 1 day and ranges from several minutes to 8 h [ 6 8 ], whereas CIH is performed on consecutive days, namely, the cumulative duration of CIH lasts more than 1 day [ 8 10 ]. AIH could induce increased ventilatory responses in rats [ 7 ] and humans [ 11 ], which can be enhanced by CIH, but cannot be elicited by sustained hypoxia [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%